La Gestión Administrativa y su Impacto en la Ejecución Presupuestaria del Cuerpo de Bomberos, Babahoyo. 2022 - Carrera Morante, Karla María (2023)
This research shows the way in which a type of analysis will be carried out in order to know if there is adequate use of the resources granted to the institution. The strategy used will allow pertinent and timely budget execution to lead to adequate administration and therefore better performance of the Cuerpo de Bomberos Babahoyo. Within the present study it is evident that there is no correct link between the departments for an efficient execution of the processes, so it was determined that the lack of management in the administrative field influences the budget execution of the institution since there is no a follow-up to the planning carried out.